Enclosures solutions, studies of acoustic effectiveness under real conditions - SIKORA, J. (Archives of Acoustics, 1996)
This reports presents examples of enclosures designed by the author and implemented in the industry. Their purpose is to limit the excessive noisiness of machines and installations that are situated outside of proeduction halls and of technological objects and increase the acoustic degradation of the environment. The results of verification studies executed in order to determine both the acoustic effectiveness of the enclosures applied and the limitation of the noise in the external environment obtained in acoustic protected sites in the neighbourhood of industrial objects are also discussed. The examples of implementation presented confirm the great usefulness and effectiveness of enclosures in anti-noise protection. This report contains also information about experimental studies conducted by the author in order to determine the influence of materials and constructional solutions on the acoustic effectiveness of enclosures. The results of research obtained are useful in designing improved constructional solutions of enclosures.